2018
DOI: 10.14260/jemds/2018/334
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Alcohol Use in Undergraduate Medical Students in a Private Medical College

Abstract: BACKGROUND Depression can significantly hamper academic performance and can also lead to substance use and abuse. The various causes leading to depression in medical students along with the multiple factors for alcohol use, needs to be assessed in view of rising levels of psychiatric morbidity. Aim-To study the relationship between depression and alcohol use among undergraduate medical students. MATERIALS AND METHODSA cross-sectional study was done on 428 undergraduate students in a private medical college in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Some studies reported the prevalence of AUDs and defined them using standardised tools (Alcohol Use Disorder Identification Test [AUDIT], CAGE questionnaire, Alcohol, Smoking and Substance Involvement Screening Test [ASSIST]), ICD 10 criteria or bespoke definitions. Among medical students (18–23 years) who were drinkers, the prevalence of hazardous drinking was 19.29% (Anandi et al ., 2018 ), alcohol dependence was 3.7–10% (Kundapur and Kodyalamoole, 2016 ; Haorongbam et al ., 2018 ), binge drinking 14–30% (Kundapur and Kodyalamoole, 2016 ; Anandi et al ., 2018 ) and ‘problem drinking’ (not defined) was 41.46% (Garg et al ., 2009 ). Among students of classes 8, 10 and 12 (12–19 years), 1.6% (2% males, 0% females) of lifetime users had alcohol dependence (Jaisoorya et al ., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported the prevalence of AUDs and defined them using standardised tools (Alcohol Use Disorder Identification Test [AUDIT], CAGE questionnaire, Alcohol, Smoking and Substance Involvement Screening Test [ASSIST]), ICD 10 criteria or bespoke definitions. Among medical students (18–23 years) who were drinkers, the prevalence of hazardous drinking was 19.29% (Anandi et al ., 2018 ), alcohol dependence was 3.7–10% (Kundapur and Kodyalamoole, 2016 ; Haorongbam et al ., 2018 ), binge drinking 14–30% (Kundapur and Kodyalamoole, 2016 ; Anandi et al ., 2018 ) and ‘problem drinking’ (not defined) was 41.46% (Garg et al ., 2009 ). Among students of classes 8, 10 and 12 (12–19 years), 1.6% (2% males, 0% females) of lifetime users had alcohol dependence (Jaisoorya et al ., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among medical students (22-23 years), 44% considered it safe to consume alcohol, and 88% believe drinking patterns are mood-dependent (Kundapur and Kodyalamoole, 2016). In medical students (17-23 years), reasons for initiation of drinking included curiosity (19.6%), attending a party (17.5%), friends' influence (15.2%) and social gatherings (9.8%); and reasons for continued use included enjoyment (31.5%), as a coping mechanism for depressive symptoms (17.8%), socialisation (14.8%) and to take mind off other issues (9.6%) (Haorongbam et al, 2018). Among college-going students (mean age 16.7 years; S.D.…”
Section: Knowledge and Attitudesmentioning
confidence: 99%